Bahasa Inggris - Taufikin Taufikin; Lift Anis Ma'shumah (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2021)
The study aims to analyze the concept of independent education in Ki Hadjar Dewantara’s (KHD) perspective and determine its relevance to the independent learning policy implemented in Indonesia. This study is a literature review of character analysis with the main objective of profoundly investigating KHD’s concept of education about independent education through documentation studies and interviews, which were then analyzed using Content Analysis. According to the findings of this study, KHD presents the concept of independent education, starting from the purpose of educating students to liberate them esoterically, mentally, and physically by implementing Pancadarma, which is implemented in Taman Siswa, with among system using various methods that are continuously carried out from an early childhood to adulthood presented in the Taman Siswa. The concept of KHD’s independent education is relevant to that of independent learning in Indonesia today, in terms of its purposes, education system, teachers, and students.